Diagnostic Reference Levels for Diagnostic and Interventional X-Ray Procedures in Germany: Update and Handling - Schegerer, Alexander; Loose, Reinhard; Heuser, Lothar J.; Brix, Gunnar (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose Recent developments in medical technology have broadened the spectrum of X-ray procedures and changed exposure practice in X-ray facilities. For this reason, diagnostic reference levels (DRLs) for diagnostic and interventional X-ray procedures were updated in 2016 and 2018, respectively. It is the aim of this paper to present the procedure for the update of the DRLs and to give advice on their practical application.Materials and Methods For the determination of DRLs, data from different independent sources that collect dose-relevant data from different facilities in Germany were considered. Seven different weight intervals were specified for classifying pediatric X-ray procedures. For each X-ray procedure considered, the 25th, 50th, and 75th percentile of the respective national distribution of the dose-relevant parameters were determined. Additionally, effective doses that correspond to the DRLs were estimated.Results In procedures with already existing DRLs before 2016, the values were lowered by circa 20 % on average. Numerous DRLs were established for the first time (9 for interventional procedures, 10 for CT examinations).Conclusion For dose optimizations even below the new national DRLs, the BfS recommends establishing local reference levels, using dose management software (particularly in CT and interventional radiology), adapting dose-relevant parameters of X-ray protocols to the individual patient size, and establishing internal radiation protection teams responsible for optimizing X-ray procedures in clinical practice. When applying good medical practice and using modern equipment, the median dose values of the nationwide dose distributions can not only be easily achieved but can even be undercut.Key Points:Citation FormatZiel Die Entwicklungen der Medizintechnik in den letzten Jahren haben das Spektrum medizinischer Röntgenanwendungen erweitert und die Untersuchungspraxis in Röntgeneinrichtungen verändert. Infolgedessen wurden 2016 und 2018 die diagnostischen Referenzwerte (DRW) für diagnostische bzw. interventionelle Röntgenanwendungen aktualisiert. Ziel dieser Arbeit ist es, das Prozedere der Aktualisierung und die aktualisierten DRW vorzustellen sowie Hinweise zu ihrer praktischen Anwendung zu geben.Material und Methoden Für die Aktualisierung der DRW wurden verschiedene, voneinander unabhängige Datenquellen berücksichtigt, die Dosis-relevante Untersuchungsparameter von verschiedenen Einrichtungen aus dem gesamten Bundesgebiet registrieren. Röntgenanwendungen an Kindern wurden in 7 verschiedene Gewichtsklassen eingeteilt. Für jede erfasste Röntgenanwendung wurde die 25., 50. und 75. Perzentile der entsprechenden nationalen Verteilung der Dosis-relevanten Untersuchungsparameter bestimmt. Für die aktualisierten und neu festgelegten DRW wurden die zugehörigen effektiven Dosiswerte abgeschätzt.Ergebnisse Die DRW für Röntgenanwendungen, die schon vor 2016 existierten, konnten im Mittel um circa 20 % gesenkt werden. Für zahlreiche Röntgenanwendungen wurden neue DRW festgelegt (für die interventionelle Radiologie 9, für die Computertomografie 10).Schlussfolgerungen Um Röntgenanwendungen auch unterhalb der neuen nationalen DRW zu optimieren, empfiehlt das BfS, lokale Referenzwerte festzulegen und anzuwenden, Dosismanagementsoftware (v. a. für den Bereich der CT und interventionellen Radiologie) einzusetzen, Dosis-relevante Protokollparameter der Röntgenuntersuchung bzw. des interventionell-radiologischen Eingriffs systematisch an die Patientenstatur anzupassen und einrichtungsinterne Strahlenschutzteams zu etablieren. Bei guter Praxis und Einsatz moderner Geräte-Technologien können die durch die 50. Perzentile der nationalen Verteilungen vorgegebenen Expositionsniveaus erreicht und sogar unterschritten werden.Kernaussagen:Zitierweise
Keywords: patient exposure; dose optimization and reduction; diagnostic reference levels (DRLs); diagnostic and interventional radiology; pediatric X-ray examinations